Pemanfaatan Serat Spanduk Bekas Sebagai Bahan Tambahan Pada Campuran Beton - Handika Setya Wijaya; Diana Ningrum; Galih Damar Pandulu; Jeronimo De Deus; Raymond Valiant (Institut Teknologi Garut, 2025)
The banner will be taken down after the permit expires, leaving only a pile of trash in its place. This study investigates the compressive strength and tensile strength of concrete through the addition of banner fiber waste in concrete mixtures with various percentages, namely 0%, 1%, 3%, and 5%. The method used is an experiment in a quantitative research approach. The test specimens made in this experiment are concrete cylinders. The results of the study on the variation of plastic banner waste addition in the form of rectangular pieces and percentage variations of 0%, 1%, 3%, and 5% yielded an average compressive strength of 0% (normal concrete) of 18.284 MPa. The addition of 1% plastic banner waste resulted in an average compressive strength of 15.338 MPa. The average compressive strength was 13.947 MPa with the addition of 3% plastic banner waste. And with the addition of 5% plastic banner fiber waste, the average compressive strength value was 5,420 MPa. Thus, it can be concluded that concrete with 0% plastic banner fiber waste (normal concrete) has a better compressive strength value compared to concrete with 1%, 3%, and 5% plastic banner fiber waste.